The Role of Interference in Implicit Learning of the Stroop Stimuli Sequence - Сергей Н. Бурмистров; Андрей Ю. Агафонов; Арина Д. Фомичева; Юрий Е. Шилов (Российский психологический журнал, 2021)
Introduction. The effect of interference can help identify essential characteristics of the process of acquiring new knowledge. This study is the first to provide empirical evidence on the use of the effect of interference to dissociate explicit and implicit learning. We tested the hypothesis that the effect of interference arising in response to the Stroop test stimuli reduces the efficiency of explicit sequence learning and does not significantly affect implicit sequence learning.